Bee and bee products allergy in Turkish beekeepers: determination of risk factors for systemic reactions - Celikel, S; Karakaya, G; Yurtsever, N; Sorkun, K; Kalyoncu, A F (Allergologia et immunopathologia, 2006)
The prevalence of allergic reactions due to bee stings in beekeepers varies in different regions of the world. The aim of this study was to evaluate the characteristics of sting reactions and the risk factors for developing systemic reactions in Turkish beekeepers. A self-administered questionnaire was distributed to 1250 beekeepers to be completed in seven different cities of Turkey. A total of 494 (39.6 %) questionnaires were returned. There were 444 subjects (89.9 %) with a history of sting exposure in the previous 12 months. Systemic reactions were present in 29 subjects (6.5 %) and nine (2 %) reactions were anaphylactic. Fifty-five percent of beekeepers reported more than 100 bee stings in the previous year. When systemic reactions were controlled by age and duration of beekeeping in a logistic regression model, seasonal rhinitis (OR: 4.4, 95 % CI: 1.2-11.5), perennial rhinitis (OR: 4.6, 95 % CI: 1.2-18.2), food allergy (OR:7.0, 95 % CI: 2.0-25.0), physician-diagnosed asthma (OR: 8.0, 95 % CI: 2.5-25.6), having an atopic disease of any type (OR: 3.3, 95 % CI: 1.2-8.7) and having two or more atopic diseases (OR: 10.9, 95 % CI: 3.5-33.8) were significantly associated with systemic reactions due to bee sting in the previous 12 months. The incidence of systemic reactions in Turkish beekeepers is low, which might be due to the protective effect of a high frequency of bee stings. The risk of systemic reactions increases approximately three-fold when one atopic disease is present and eleven-fold when two or more concurrent atopic diseases are present with respect to no atopic disease.